2022
DOI: 10.1101/2022.07.25.501344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leptospira interrogans prevents macrophage cell death and pyroptotic IL1β release through its atypical lipopolysaccharide

Abstract: Leptospira interrogans are bacteria that can infect all vertebrates and are responsible for leptospirosis, a neglected zoonosis. Some hosts are susceptible to leptospirosis whereas mice are resistant and get chronically colonized. Although leptospires escape recognition by some immune receptors, they activate NLRP3-inflammasome and trigger IL1β secretion. Classically, IL1β secretion is associated with lytic inflammatory cell death called pyroptosis, resulting from cytosolic LPS binding to inflammatory caspases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Indeed, we previously showed that leptospiral LPS avoids human TLR4 and mouse TLR4-TRIF activation. Recently, through the atypical structures of its lipid A and O antigen [11, 47, 48], LPS has also been shown to prevent cell death by pyroptosis. Therefore, it was not surprising to attribute the autophagy modulation phenotype to leptospiral LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we previously showed that leptospiral LPS avoids human TLR4 and mouse TLR4-TRIF activation. Recently, through the atypical structures of its lipid A and O antigen [11, 47, 48], LPS has also been shown to prevent cell death by pyroptosis. Therefore, it was not surprising to attribute the autophagy modulation phenotype to leptospiral LPS.…”
Section: Discussionmentioning
confidence: 99%